Klasyfikacja metod analizy zależności przyczynowych w ekonomii - Osińska, Magdalena (The Classification of the Methods of Causality Analysis in Economics, 2009)
In the paper, we discuss and compare several concepts of causality analysis in economics, e.g. Simon's, Hover's, Granger's and some others. They are considered within philosophical as well as methodological frameworks. We take into account the methods of analysis that are divided into econometric and non-econometric. We end with the classification of the methodology, as well as underlying concepts. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 24-32